Antibiotic consumption in laboratory confirmed vs. non-confirmed bloodstream infections among very low birth weight neonates in Poland - A. Różańska; J. Wójkowska-Mach; P. Adamski; M. Borszewska-Kornacka; E. Gulczyńska; M. Nowiczewski; E. Helwich; A. Kordek; D. Pawlik; M. Bulanda (BMC, 2017)
Abstract Background Newborns are a population in which antibiotic consumption is extremely high. Targeted antibiotic therapy should help to reduce antibiotics consumption. The aim of this study was an assessment of antibiotic usage in bloodstream infections treatment in the Polish Neonatology Surveillance Network (PNSN) and determining the possibility of applying this kind of data in infection control, especially for the evaluation of standard methods of microbiological diagnostics. Methods Data were collected between 01.01.2009 and 31.12.2013 in five teaching NICUs from the PNSN. The duration of treatment in days (DOT) and the defined daily doses (DDD) were used for the assessment of antibiotics consumption. Results The median DOT for a single case of BSI amounted to 8.0 days; whereas the median consumption expressed in DDD was 0.130. In the case of laboratory confirmed BSI, median DOT was 8 days, and consumption-0.120 DDD. Median length of therapy was shorter for unconfirmed cases: 7 days, while the consumption of antibiotics was higher-0.140 DDD (p < 0.0001). High consumption of glycopeptides expressed in DOTs was observed in studied population, taking into account etiology of infection. Conclusions Even application of classical methods of microbiological diagnostics significantly reduces the consumption of antibiotics expressed by DDD. However, the high consumption of glycopeptides indicates the necessity of applying rapid diagnostic assays. Nevertheless, the assessment of antibiotic consumption in neonatal units represents a methodological challenge and requires the use of different measurement tools.